2018
DOI: 10.1007/s40858-018-0252-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of bean yield and Fusarium root rot biocontrol using mixtures of Bacillus, Pseudomonas and Rhizobium

Abstract: During a screening of beneficial rhizobacteria strains with capability of suppressing Fusarium root rot and improving bean yield, 680 bacteria belonging to Bacillus, fluorescent and non-fluorescent Pseudomonas, and Rhizobium were isolated from commercial field soils and plant root nodules in Zanjan province, Iran. Of these, two hundred representative isolates were biochemically characterized and screened in vitro for inhibiting mycelia growth of Fusarium solani f. sp. phaseoli. Sixteen rhizobacteria isolates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(22 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…For the compatibility test between bacteria, the formation of inhibition halo was not observed, which reports that these microorganisms are not antagonistic to each other, making it possible to co-inoculate these strains, a trend demonstrated in recent decades (Cassan et al, 2009;Kalantari et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…For the compatibility test between bacteria, the formation of inhibition halo was not observed, which reports that these microorganisms are not antagonistic to each other, making it possible to co-inoculate these strains, a trend demonstrated in recent decades (Cassan et al, 2009;Kalantari et al, 2018).…”
Section: Resultsmentioning
confidence: 97%
“…At the same time, co-inoculation between bacterial species, such as Rhizobium sp., Azotobacter sp., Pseudomonas sp., Bacillus sp., and others, have shown various benefits in plants and cultivations systems, such as the crops succession between leguminous and grassy plants or, in a consortium system between grasses and forages (Cassan et al, 2009;Marks et al, 2015;Kalantari et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The decomposer bacteria are reported to suppress pathogenic bacteria and fungi due to metabolites produced from them. There was a report that decomposer bacteria such as pseudomonads produced metabolite, which could suppress the fungal disease of important plants ( Dowling and O'Gara, 1994 ; Kalantari et al, 2018 ). The decomposer bacteria reported to win the pathogenic bacteria in competition and in the place where decomposers bacteria are there, the disease-causing bacteria cannot survive.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that Bacillus with other biocontrol agents brings benefits to the plant, both for growth and nutrition, minimizing the effects of adverse conditions. Therefore, the use of beneficial agents that play on multiple fronts can be considered a useful technological resource for farmers, either by promoting plant growth or by its disease-preventing action (Kalantari et al 2018;Moreira et al 2021).…”
Section: Introductionmentioning
confidence: 99%